2004
DOI: 10.1016/s0896-6273(04)00761-5
|View full text |Cite
|
Sign up to set email alerts
|

Synapse to Nucleus Signaling during Long-Term Synaptic Plasticitya Role for the Classical Active Nuclear Import Pathway

Abstract: The requirement for transcription during long-lasting plasticity indicates that signals generated at the synapse must be transported to the nucleus. We have investigated whether the classical active nuclear import pathway mediates intracellular retrograde signal transport in Aplysia sensory neurons and rodent hippocampal neurons. We found that importins localize to distal neuronal processes, including synaptic compartments, where they are well positioned to mediate synapse to nucleus signaling. In Aplysia, sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 7 publications
3
78
1
Order By: Relevance
“…To conclude, our data clearly reveal some interactions between synaptic activity and circadian oscillators and implicate oligophrenin-1 in its regulation, delineating a new means of communication between synapse and nucleus 24,36,40 . These findings are further indication 36,41 that cognitive ability is influenced by circadian rhythms, and promise to provide insight into normal plasticity and the etiology of intellectual disability.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…To conclude, our data clearly reveal some interactions between synaptic activity and circadian oscillators and implicate oligophrenin-1 in its regulation, delineating a new means of communication between synapse and nucleus 24,36,40 . These findings are further indication 36,41 that cognitive ability is influenced by circadian rhythms, and promise to provide insight into normal plasticity and the etiology of intellectual disability.…”
Section: Discussionmentioning
confidence: 54%
“…The signals generated in synapses must therefore be transported to the nucleus, and it has been shown, in sensory neurons of mollusk Aplysia and hippocampal neurons of mice, that the classical nuclear import pathway plays a critical role in transporting synaptically generated signals into the nucleus during learning-related forms of plasticity 24 . Furthermore, a recent study showed that synaptic activity induced by NMDA activation drives oligophrenin-1 into dendritic spines 12 .…”
Section: Chemically-induced Synaptic Activity Induces Rev-erbα Localimentioning
confidence: 99%
“…We previously identified an isoform of importin ␣, ApImp-␣3, in Aplysia (9). In pull-down assays in which GST-ApCREB2 was incubated with lysates of 293T cells expressing FLAG-tagged ApImp-␣3, we detected an interaction between the 2 proteins (Fig.…”
Section: Figmentioning
confidence: 82%
“…A slower, more persistent mechanism of signaling to the nucleus involves the transport of soluble molecules from stimulated synapses to the nucleus (6,7). Recent studies have indicated that this type of transport may involve the active nuclear import pathway (8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation